All Days 2010
DOI: 10.2118/137693-ms
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Gas Shales on the Micro- and Nano-Scales

Abstract: A reliable petrophysical rock classification can significantly improve production form organic-rich source rocks, which have been recognized as a major energy resource in the recent years. Complex lithology and rapid vertical variation of petrophysical and compositional properties in these reservoirs result in challenging formation evaluation and production planning. Well logs are good candidates for formation evaluation of shale-gas reservoirs as they provide measurements with a relatively high vertical resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
160
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(162 citation statements)
references
References 12 publications
2
160
0
Order By: Relevance
“…FIB and BIB), which allow imaging of mineral fabrics and porosity down to the nanometre scale in very high-quality cross sections with SEM and TEM (Lee et al, 2003;Desbois et al, 2009Desbois et al, , 2011Desbois et al, , 2013Desbois et al, , 2016Loucks et al, 2009;Curtis et al, 2010;Heath et al, 2011;Klaver et al, 2012;Keller et al, 2011Keller et al, , 2013Houben et al, 2013Houben et al, , 2014Hemes et al, 2013Hemes et al, , 2015Laurich et al, 2014;Warr et al, 2014;Song et al, 2016). Serial sectioning allows the reconstruction of microstructure in 3-D (Keller et al, 2011(Keller et al, , 2013Milliken et al, 2013;Hemes et al, 2015), and cryogenic techniques can image the pore fluid in the samples and avoid artefacts produced by drying Schmatz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…FIB and BIB), which allow imaging of mineral fabrics and porosity down to the nanometre scale in very high-quality cross sections with SEM and TEM (Lee et al, 2003;Desbois et al, 2009Desbois et al, , 2011Desbois et al, , 2013Desbois et al, , 2016Loucks et al, 2009;Curtis et al, 2010;Heath et al, 2011;Klaver et al, 2012;Keller et al, 2011Keller et al, , 2013Houben et al, 2013Houben et al, , 2014Hemes et al, 2013Hemes et al, , 2015Laurich et al, 2014;Warr et al, 2014;Song et al, 2016). Serial sectioning allows the reconstruction of microstructure in 3-D (Keller et al, 2011(Keller et al, , 2013Milliken et al, 2013;Hemes et al, 2015), and cryogenic techniques can image the pore fluid in the samples and avoid artefacts produced by drying Schmatz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on these imaging techniques can be found in Blunt et al [51]. On the other hand, other techniques including focused ion beams (FIB) and scanning electron microscopy (SEM) are essentially destructive (Tomutsa et al [52], Curtis et al [53], and Lemmens et al [54]). SEM can be used to extract two-dimensional planar images of the microstructures.…”
Section: Pore Network Modelsmentioning
confidence: 99%
“…By using these imaging methods, it is possible to receive a solid idea of a shale's internal (micro) structure and pore geometry (e.g., [6][7][8][9][10][11]). BIB milling in combination with SEM imaging delivers direct information about pore sizes, their morphology and spatial distribution, rock microstructure, and potential anisotropy as well as core damage due to sample handling (e.g., [3,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]). Additionally, in combination with energy dispersive X-ray spectroscopy (EDX), BIB-SEM enables the identification of individual grains [26,27].…”
Section: Introductionmentioning
confidence: 99%